The methylation hypothesis: Do epigenetic chromatin modifications play a role in epileptogenesis? - Kobow, Katja; Blümcke, Ingmar (Epilepsia, 2011)
Any structural brain lesion can provoke epilepsy, although onset and progression of seizures as well as response to antiepileptic drug (AED) treatment remain difficult to predict in each patient. Tremendous work has focused on the development of new AED compounds with the intention to treat seizures. However, these efforts have not yet discovered a "magic bullet" that cures epilepsy in every patient or modifies disease progression. With the "methylation hypothesis" we propose that epigenetic mechanisms play a pivotal role in epileptogenesis in patients with structural lesions. "Epigenetics" is defined as information that is heritable during cell division other than the DNA sequence itself, that is, DNA methylation or histone tail modifications, which can produce lasting alterations in chromatin structure and gene expression. They are increasingly recognized as fundamental regulatory processes in central nervous system development, synaptic plasticity, and memory, and also play a role in neurologic disorders such as schizophrenia and spinal muscular atrophy. The methylation hypothesis suggests that seizures by themselves can induce epigenetic chromatin modifications, thereby aggravating the epileptogenic condition. The impact of the methylation hypothesis for new-onset epilepsy will be discussed. Unravelling of epigenetic pathomechanisms will also open new strategies to identify molecular targets for pharmacologic treatment in epilepsies.
Keywords: Epilepsy; DNA methylation; Histone modification; Epigenetic medicine